Utopian drama : in search of a genre - Adiseshiah, Siân Helen (Methuen drama engage, 2022)
"As the first full-length study to analyse utopian plays in Western drama from antiquity to the present, Utopian Drama: In Search of a Genre offers an illuminating appraisal of the objectives of utopianism as manifested in drama through the ages, and carefully ascertains the added value that live performance brings to the persuasion of utopian thought. Siân Adiseshiah scrutinises the distinctive intervention of utopian drama through its examination alongside the utopian prose tradition - in this way, the book establishes new ways of approaching utopian aesthetics and new ways of interpreting utopian drama. This book provides fresh understandings of the generic features of utopian plays, identifies the gains of establishing a new genre, and ascertains ways in which this genre functions as political theatre. Referring to over 40 plays, of which 18 are examined in detail, Utopian Drama traces the emergence of the utopian play in the Western tradition from ancient Greek Comedy to experimental contemporary work. Works discussed in detail include plays by Aristophanes, Margaret Cavendish, George Bernard Shaw, Howard Brenton, Claire MacDonald, Cesi Davidson, and Mojisola Adebayo. As well as offering extended attention to the work of these playwrights, the book reflects on the development of utopian drama through history, notes the persistent features, tropes, and conventions of utopian plays, and considers the implications of their registration for both theatre studies and utopian studies"--